Respuesta :
Answer:
-80
Step-by-step explanation:
The average rate of change is
a.r.c = f(4) - f(1)
--------------
4-1
f(4) = 244 and f(1) = 484
a.r.c = 244 - 484
--------------
3
= -240/3
=-80
Answer:
The average rate of change of f(x) from 1 to 4 is -80.
Step-by-step explanation:
The average rate of change of f(x) from a to b is defined as
[tex]m=\frac{f(b)-f(a)}{b-a}[/tex]
The average rate of change of f(x) from 1 to 4 is defined as
[tex]m=\frac{f(4)-f(1)}{4-1}[/tex]
[tex]m=\frac{f(4)-f(1)}{3}[/tex]
From the given table it is clear that the the value of the function is 244 at x=4 and 484 at x=1. So f(4)=244 and f(1)=484. Put these values in the above equation.
[tex]m=\frac{244-484}{3}[/tex]
[tex]m=\frac{-240}{3}[/tex]
[tex]m=-80[/tex]
Therefore the average rate of change of f(x) from 1 to 4 is -80.